Screening, Identification, and Quantification of Nutritional Components and Phytochemicals in Foodstuffs - Donno, Dario (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book provides readers with a good overview of the status and exciting developments in the identification of health-promoting properties and potential applications of nutraceutical substances. It includes papers focused on modern analytical instrumentation and new methods and biological tests applied to the evaluation of plant foods, derived products, herbal products, and food supplements and the phytochemical characterization of innovative natural sources of bioactive compounds and relative health-promoting properties.